A percepção da comunidade acadêmica sobre o exame nacional de cursos: o caso FEEVALE - Gehlen, Luciana (2004)
The expansion of graduate system in Brasil has reinforced discussion about teaching quality and the need of permanent evaluation by institutions and courses. The current work has the aim to propose a reflexion about the Graduate Evaluation System, specially the National one called big Exam in Business Administration Course at Centro Universitário Feevale. The lack of systematic on pertinent informations concerning to this evaluation by this institution and the need of finding out the perception of academicals community about this there were the motivating factors for this works realization. By using a qualitative research with case study, graduate among the years of 1996 to 2003 and head people from this institution linked to the above course were interviewed trying to identify how public policies of evaluation are understood. Besides that, questions such as quality on Graduate System, the evaluation of this system itself, historical basis of Graduate System in the Country as well as this institution characterization and the Business Administration course. During eight years of constant evaluation, this course has got four A s, two B s and two C s, creating discussions and need of understanding about what exactly does this mean, so that on future actions that are going to be taken, quality can be kept up.